Scope And Standards Of The Double Criminality Principle In Extradition Agreements - Indrastuti, Lusia; Rahmat, Doris (International Journal of Educational Research & Social Sciences, 2022)
The purpose of this research is to study the consistency and suitability between a law and other laws or between laws and regulations relating to the application of the double criminality principle to corruption. The research was conducted with a normative juridical research type with a statute approach. The legal approach is carried out by examining international conventions, laws and regulations related to the double criminality principle. This approach is necessary for The results of the study are an argument to solve the problems that exist in the formulation of the problem. For this reason, researchers need to find the legal ratio and ontological basis of international laws and conventions. The legislative and ontological ratios will be used as the basis for conceptualizing the implementation of the double criminality principle in the future.